A Mediastinal False Aneurysm with Aortocutaneous Fistula - ARSAN, SİNAN (My University, 2004)
Abstract In this report, we present a case of the development of a false aneurysm of the ascending aorta with an aortocutaneous fistula in a 57-year-old patient 10 months following aortic valve replacement and concomitant coronary bypass surgery.